90 miles of mirror: Reimagining cultural memory through the case of Cuban-American migrants in Miami - van de Voort, Sjamme (2021)
This thesis presents a methodological approach to cultural memory based on theories that place memory in the socio-cultural realm, employing the Cuban-American community in Miami as a case study. The research reveals the broad scope of this theoretical field and presents a methodological apparatus that incorporates the multiplicity of embedded possibilities. By examining theoretical currents underpinning the field, it becomes clear that the notion of space is a crucial theatre in which memory happens, which is why the thesis uses the concept of cartographical reasoning in its instrumentalisation of memory theory.